2014
DOI: 10.1186/1471-2164-15-1115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of codon adaptation on codon-level and gene-level translation efficiency in vivo

Abstract: BackgroundThere is a significant difference between synonymous codon usage in many organisms, and it is known that codons used more frequently generally showed efficient decoding rate. At the gene level, however, there are conflicting reports on the existence of a correlation between codon adaptation and translation efficiency, even in the same organism.ResultsTo resolve this issue, we cultured Escherichia coli under conditions designed to maintain constant levels of mRNA and protein and subjected the cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 54 publications
5
50
0
Order By: Relevance
“…These pauses are strikingly similar to those observed when chloramphenicol is added to a culture to arrest translation prior to harvesting the cells (Figure 4E). As shown previously by Mori and co-workers, chloramphenicol arrests ribosomes in a sequence-specific manner, pausing ribosomes when the same five amino acids are encoded in the E site (Nakahigashi et al, 2014). This sequence specificity was also observed by Mankin and co-workers, who detected pauses with Gly, Ser, Ala, and Thr codons in the E site using toeprinting assays, but only in the presence of chloramphenicol (Orelle et al, 2013).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…These pauses are strikingly similar to those observed when chloramphenicol is added to a culture to arrest translation prior to harvesting the cells (Figure 4E). As shown previously by Mori and co-workers, chloramphenicol arrests ribosomes in a sequence-specific manner, pausing ribosomes when the same five amino acids are encoded in the E site (Nakahigashi et al, 2014). This sequence specificity was also observed by Mankin and co-workers, who detected pauses with Gly, Ser, Ala, and Thr codons in the E site using toeprinting assays, but only in the presence of chloramphenicol (Orelle et al, 2013).…”
Section: Resultsmentioning
confidence: 57%
“…Earlier studies distributed information about the position of the ribosome over multiple nucleotides at the center of reads, blurring the signal (Li et al, 2012; Oh et al, 2011). We and others found that by assigning ribosome occupancy to the 3’-end of the reads, we obtain a more precise measurement of ribosome position (Balakrishnan et al, 2014; Nakahigashi et al, 2014; Woolstenhulme et al, 2015). With this higher resolution, we see that the previously observed enrichment of ribosome occupancy at SD motifs can explained by pauses at Gly codons and by failure to isolate the entire population of ribosome-protected mRNA fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Because CHL has been traditionally viewed as a universal inhibitor of peptide bond formation, it has been used to "freeze" the ribosomes on mRNA in some profiling experiments (30,35), an approach challenged by several studies where trends similar to the ones we presented here were noted (29,31,36,37). We show that exposure of the cells to high concentrations of CHL (or LZD) does not in fact freeze the ribosomes on mRNA, but allows them to redistribute from the sites less favorable for the drug-dependent arrest to the downstream strong-arrest codons.…”
Section: Discussionmentioning
confidence: 96%
“…complexes, biased conversion of the mRNA fragments into complementary DNAs, and procedures for aligning the ribosomeprotected base sequences (9,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). These considerations underscore the importance of profiling the translation progression directly.…”
Section: Significancementioning
confidence: 99%